The global human settlement layer sets a new standard for global urban data reporting with the urban centre database - Melchiorri, Michele (Frontiers in Environmental Science, 2022)
The monitoring of the Sustainable Development Goals requires a wealth of updated, reliable and comparable data on the planet Earth, on societal activities and society-environment interactions. Despite the massive big data archives available already today, salient data are missing for key thematic domains and geographical areas. Even for cities, the most prominent manifestations of human agglomeration, data are scarce, sectoral and scattered. Earth observation may help reconciling the disparity between data-rich and data-poor territories. The Global Human Settlement Layer project of the European Commission has generated an open source global dataset on cities –the Global Human Settlement Urban Centre Database (GHS-UCDB). The database describes more than 10,000 Urban Centres in 2015 with their location, extent, and a set of geographical, socio-economic and environmental attributes, with multi-temporal data records (covering up to a time span of 40 years). The database combines information extracted from satellite imagery with physical and socio-economic information from a number of voluminous and heterogeneous sources made available by researchers and institutions as open geospatial data. The paradigm introduced with the GHS-UCDB relies on massive geospatial data integration and harmonisation carried out in GIS environment (mainly via spatial joins and zonal statistics). The range and depth of geospatial and statistical variables in this dataset represent a new standard foundation for information on cities - more than doubling the number of cities usually reported by international organisations, offering the capacity to understand dynamics, e.g. on population, greenness, economic productivity, night-time light and pollutant emissions. Moreover, the database offers the basis to estimate SDG indicators and other essential variables for the Post 2015 Development Agenda.